PyParadigm—A Python Library to Build Screens in a Declarative Way - Knorr, Felix G.; Petzold, Johannes; Marxen, Michael (Frontiers in Neuroinformatics, 2019)
In experimental psychology, subjects are confronted with computer-based experimental paradigms. Creating such paradigms can require quite an effort. PyParadigm is a newly developed Python library to ease the development of such paradigms by employing a declarative approach to build user interfaces (UIs). This approach is a highly code-efficient alternative to currently available libraries. Although PyParadigm was initially developed for the creation of experimental paradigms, it is generally suited to build UIs that display or interact with 2D objects.